2000
DOI: 10.1046/j.1365-8711.2000.03090.x
|View full text |Cite
|
Sign up to set email alerts
|

Broadening of lines of Be II, Sr II and Ba II by collisions with hydrogen atoms and the solar abundance of strontium

Abstract: In a previous paper by the present authors the theory of Anstee and O’Mara for the broadening of spectral lines of neutral atoms by collisions with hydrogen atoms was extended to singly ionized atoms. In this paper we apply the method to the resonance and triplet lines of ionized strontium, the infrared triplet of ionized barium, and the resonance lines of ionized beryllium. Analysis of five lines of ionized strontium, previously regarded as too strong for an abundance analysis, and two lines of neutral stront… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 28 publications
4
33
2
Order By: Relevance
“…We estimated γ 6 using the Deridder & van Rensbergen (1976) approach with enhancement factor E = 1.5. In agreement with the conclusion of Mashonkina & Zhao (2006) we found that the recent calculations of the collisional damping constant made by Barklem & O'Mara (2000) overestimate γ 6 for this line by a factor 1.5. The near line wings are sensitive as well to the value of microturbulent velocity, while the line core is affected by the macroturbulence.…”
Section: One-dimensional Casesupporting
confidence: 91%
“…We estimated γ 6 using the Deridder & van Rensbergen (1976) approach with enhancement factor E = 1.5. In agreement with the conclusion of Mashonkina & Zhao (2006) we found that the recent calculations of the collisional damping constant made by Barklem & O'Mara (2000) overestimate γ 6 for this line by a factor 1.5. The near line wings are sensitive as well to the value of microturbulent velocity, while the line core is affected by the macroturbulence.…”
Section: One-dimensional Casesupporting
confidence: 91%
“…A striking excess of beryllium as compared with lithium is found in our Sun, since beryllium is rapidly destroyed by thermonuclear reactions at temperatures above 3.6 × 10 6 K, and its abundance also constraints on mixing between photospheric and deeper regions of stars, which is of particular interest in the Sun (Balachandran & Bell 1998). The surface contents of light elements, especially beryllium, provide information on nucleogenesis, and it almost relies on the Be II resonance doublet at 3130 Å, which emphasizes the importance of these lines in our present work (Barklem & O'Mara 2000). Moreover, Be II line profiles are of interest for opacity calculations (Dimitrijević & Sahal-Bréchot 1992).…”
Section: Introductionmentioning
confidence: 58%
“…Barklem & O'Mara 2000;Zethson et al 2001). Most recently, with the aid of these six Sr II lines, NLTE stellar strontium abundances have been derived by serval authors (Andrievsky et al 2011;Bergemann et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…4.2.2). Whenever possible, we use damping constants as calculated by Anstee & O'Mara (1995), which have proved to be quite accurate (Anstee et al 1997;Barklem & O'Mara 2000).…”
Section: Abundance Analysis After Continuum Re-normalisation (Methods C)mentioning
confidence: 99%